Monitoring Soil Moisture and Freeze/Thaw State Using C-band Imaging Radar - Tang, Wen (University of Waterloo, 2015)
Soil moisture is an important state variable in many hydrological and meteorological applications. This thesis explores the use of the C-band synthetic aperture radar (SAR) parameters to monitor soil moisture and freeze/thaw state in a cold-season hydrologic environment. The circular-linear compact polarimetric (CP) configuration is considered as a possible alternative of the quad polarimetric (QP) system because it acquires images with wider swath and reduced complexity, cost and energy requirement of the radar system while maintaining the information content of the acquired imagery. In this study, 15 RADARSAT-2 QP images were acquired from October 2013 to June 2014 and CP images were simulated from each RADARSAT-2 QP imagery acquired. Field measurements of soil properties were collected along with the radar imagery acquisitions. The backscattering coefficients in all polarizations were able to discriminate frozen and unfrozen soils. But their correlations with soil moisture content were weak if examining frozen or unfrozen soils separately. The Oh et al. (1992) model was implemented in this study to compare with acquired RADARSAT-2 data. A good agreement was found between the linear polarimetric backscattering coefficients simulated by the Oh model and the RADARSAT-2 data, indicating that the study site even with 10 cm tall standing hay was consistent with a bare soil site at C-band and the Oh model can be applied to frozen soils. With respect to CP parameters, the first and fourth Stokes parameters and m-δ surface and volume scattering components can detect soil freeze/thaw state and have potential for frozen/unfrozen soils mapping. The influence of vegetation on selected CP parameters was also evident in this study. Results demonstrated the utility of C-band radar in detecting soil freeze/thaw state rather than monitoring the changes of soil moisture content. More image acquisitions during the freezing and thawing periods, continuous field measurements of soil moisture and state, and ground measurements collected over wider study area can help further develop understanding of the CP parameters and facilitate future use of the CP mode. The contribution of this thesis is to provide better understanding of the CP parameters at a specific site and to demonstrate that CP parameters can replicate QP SAR variables to detect surface soil conditions.
Keywords: C-band SAR; RADARSAT-2; Quad polarimetry; Compact polarimetry; Soil moisture; Freeze/thaw; Oh model; Stokes vector; Geography